Perbandingan GCS dan Four Score dalam Penilaian Kesadaran pada Pasien: a Scoping Review - Wulan Puspita Sari; Cecep Eli Kosasih; Etika Emaliyawati (Universitas Malahayati, 2025)
ABSTRACT Assessing patient consciousness is an important component of medical practice, with the Glasgow Coma Scale (GCS) and the FOUR Score being the most commonly used assessment scales. However, the comparison of these two scales in various medical contexts still raises questions about the advantages and disadvantages of each scale. This study aims to conduct a scoping review of the comparison of the GCS and the FOUR Score in examining patient consciousness. This study uses a scoping review approach. Articles were obtained from three databases, namely PubMed, CINAHL, and Scopus, with keywords related to the GCS and the comparison of the FOUR Score. Inclusion criteria include research articles that compare the two assessment scales. Data analysis was carried out using a qualitative descriptive method. The results of this scoping review identified 6 articles that discussed the comparison of the GCS and the FOUR Score in examining patient consciousness. The variation in research results was influenced by the characteristics of the patient population, the time of evaluation, and differences in research methodology. This shows the importance of understanding the strengths and weaknesses of each assessment scale in the context of clinical practice. The implications of these findings for patient management and recommendations for future research are also discussed. A holistic approach to patient assessment and the need for further research to deepen the understanding of both awareness assessment scales. Keywords: FOUR Score, GCS, Awareness ABSTRAK Penilaian kesadaran pada pasien merupakan komponen penting dalam praktik medis, dengan Glasgow Coma Scale (GCS) dan FOUR Score merupakan skala penilaian yang umum digunakan. Namun perbandingan kedua skala ini dalam berbagai konteks medis masih menimbulkan pertanyaan mengenai kelebihan dan kekurangan masing-masing skala. Penelitian ini bertujuan untuk melakukan scoping review perbandingan GCS dan FOUR Score dalam pemeriksaan kesadaran pasien. Penelitian ini menggunakan pendekatan scoping review. Artikel diperoleh dari tiga database yaitu PubMed, CINAHL, dan Scopus, dengan kata kunci terkait GCS dan perbandingan FOUR Score. Kriteria inklusi mencakup artikel penelitian yang membandingkan dua skala penilaian. Analisis data dilakukan secara deskriptif kualitatif. Hasil scoping review ini mengidentifikasi 6 artikel yang membahas tentang perbandingan GCS dan FOUR Score dalam pemeriksaan kesadaran pada pasien. Variasi hasil penelitian tersebut dipengaruhi oleh karakteristik populasi pasien, waktu evaluasi, dan perbedaan metodologi penelitian. Hal ini menunjukkan pentingnya memahami kekuatan dan kelemahan setiap skala penilaian dalam konteks praktik klinis. Implikasi dari temuan ini terhadap manajemen pasien dan rekomendasi untuk penelitian di masa depan juga dibahas. Pendekatan holistik terhadap penilaian pasien dan perlunya penelitian lebih lanjut untuk memperdalam pemahaman tentang kedua skala penilaian kesadaran. Kata Kunci: FOUR Score, GCS, Kesadaran